Moda Pernambuco: uma plataforma de divulgação, fomento e capacitação de marcas de moda em Pernambuco. - Ribeiro, Mariana de Araújo (2020)
The present work elaborated on how to create conditions for the development of an online platform, here called "Moda Pernambuco", dedicated to serving both local entrepreneurs and their brands and consumers interested in consuming artisanal fashion locally, as well as services and information that converge for these two distinct target audiences, now separated, each seeking their identification. For this, it was necessary to invest in a bibliographic review focused on topics such as concepts of Creative Industries and their uses for local markets, strengthening of networks, activity consumption, branding, marketing and, specifically, fashion marketing. Among the applied methodologies are qualitative research, with in-depth interviews and netnography. From these elements, you can understand how the independent fashion brands in Pernambuco are getting stronger, using branding, communication and entrepreneurship techniques; an attempt was also made to identify which form of disclosure was most used to reach customers and identify loyal customers; and, based on these issues, a virtual platform must offer small local fashion businesses to contribute to their business. Four fashion brands from Pernambuco were selected, two that obtained institutional support to develop and two that signed without such monitoring, and recorded in-depth interviews with those responsible for them, in addition to following the interactions with these brands with their audiences on social digital Instagram network. This work resulted in guidelines for building not only the Moda Pernambuco platform, but a business based on information, consultancy and scenario analysis, as it is perceived that this market is little explored in the State and there is a lack and lack of knowledge on the part of fashion entrepreneurs for these themes, which are essential for the development and sustainability of brands.